A Note on a Formula of Riordan Involving Harmonic Numbers - Alonso-Carreón, J. A.; López-Bonilla, J.; Thapa, Gyan Bahadur (Journal of the Institute of Engineering, 2020)
We employ Stirling numbers of the second kind to prove a relation of Riordan involving harmonic numbers.